NANOSIZED CARBON-RICH GRAINS IN CARBONACEOUS CHONDRITE METEORITES - Garvie L.A.J.; Buseck P.R. (My University, 2004)
Macromolecular carbonaceous material is common in primitive meteorites. Little information exists on its form and composition, and there are no published data on nanometer-scale chemical and structural variations. Transmission electron microscopy (TEM) studies of CM meteorites reveal abundant, previously unrecognized nanosized carbonaceous grains. They have a high aromatic component as revealed by electron energy-loss spectroscopy (EELS), with up to 20 at.% substituted by S, N, and O. They occur as discrete hollow and solid nanospheres and sparse nanotubes. The grains exhibit considerable variations in composition, size, morphology, and abundance among meteorites and may represent materials from multiple reservoirs.